Christian Values in Young Learners Education - Beata Wołosiuk (Nicolaus Copernicus University in Toruń, 2011)
This article is devoted to the role of family environment in shaping the values of a young learner. A child's personality is set at an early school age. It is a special period of a child's susceptibility to formative influences and his increased cognitive curiosity. A theoretical section of the article explicates the notion of Christian values and looks at the process of values-oriented education as well at as the role of family environment in values-oriented education of young learners. The empirical section of the article presents findings of research into Christian values-oriented education of young learners. The research was carried out involving 310 grade three students and 310 parents. The research has proven that family plays a crucial role in valuesoriented education of young learners. The parents have viewed God, family and patriotism as prime values in their lives. The children have made a choice of the values similar to those which their parents hold in high regards (God, family, patriotism).